2023
DOI: 10.3389/fpls.2022.1099856
|View full text |Cite
|
Sign up to set email alerts
|

Application of chloroplast genome in the identification of Phyllanthus urinaria and its common adulterants

Abstract: BackgroundPhyllanthus urinaria L. is extensively used as ethnopharmacological material in China. In the local marketplace, this medicine can be accidentally contaminated, deliberately substituted, or mixed with other related species. The contaminants in herbal products are a threat to consumer safety. Due to the scarcity of genetic information on Phyllanthus plants, more molecular markers are needed to avoid misidentification.MethodsIn this study, the complete chloroplast genome of nine species of the genus Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Several molecular studies have demonstrated the high identification capability of cp genetic markers in distinguishing Phyllanthus and Isodon species [ 15 , 28 ]. Four regions ( matK-rps16 , ndhC-trnV-UAC , psbE-petL , and rps16-trnQ-UUG ) have been filtered as candidate molecular markers for discriminating S. baicalensis from its common adulterants in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several molecular studies have demonstrated the high identification capability of cp genetic markers in distinguishing Phyllanthus and Isodon species [ 15 , 28 ]. Four regions ( matK-rps16 , ndhC-trnV-UAC , psbE-petL , and rps16-trnQ-UUG ) have been filtered as candidate molecular markers for discriminating S. baicalensis from its common adulterants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…NGS QC Toolkit v. 2.3.3 software was utilized to obtain clear reads by trimming paired-end sequence reads. De novo assemblies and annotation of the cp genomes were performed by using GetOrganelle v. 1.6.4 and online tools CpGAVAS2 [ 13 , 39 ] and GeSeq [ 28 , 40 ] with the parameter sets referred to previous studies [ 15 , 41 ], respectively. The Apollo rectified intron/exon boundaries and start/stop codons [ 9 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total DNA was extracted using a small plant DNA Extraction Kit (Omega Bio-Tek, USA). Then we randomly broke qualified DNA samples using an ultrasonic crusher (Covaris, USA), and then completed the whole library preparation through the steps of end repair, adding A-tailing, adding sequencing connector, purification, and PCR amplification [ 21 ]. The qualified library was sequenced using the Illumina high-throughput sequencing platform (Illumina, NovaSeq 6000, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The development of barcoding markers has greatly advanced our understanding of the relationships between morphologically similar species; however, it has been revealed that Swertia is strongly paraphyletic to other genera within the Gentianaceae family (Chassot et al 2001; Xi et al 2014). Recently, the chloroplast genome has been widely used in plant system evolution, related species identi cation, genetic diversity analysis, chloroplast genetic engineering, and other applications due to the development of high-throughput sequencing technology (Yang et al 2016;Li et al 2021;Fang et al 2023;Nyamgerel et al 2023). The chloroplast genome (plastome) has a conserved structure, encodes 120-130 genes, most of which encode part of the photosynthetic apparatus of the organelle (Jensen and Leister, 2014), and is maternally inherited (Wicke et al 2011).…”
Section: Introductionmentioning
confidence: 99%